Estágio supervisionado na Educação Básica/ Ensino Fundamental I: uma experiência bragantina - SILVA, Suely Marques da (2024)
The Supervised Internship is relevant for teacher training because it allows the connection between theory and practice to actually be made, promoting professional development, through educational praxis, based on an epistemology of practice. It is worth highlighting that the aforementioned Internship took place at Escola Municipal de Ensino Fundamental Prof. Jorge Daniel Souza Ramos, located on Avenida Santos Dumont, Perpétuo Socorro in Bragança/PA, in the morning shift, from 09/05/2023 to 09/22/2023. The objective of this study is to understand the theory-practice relationship in the classroom, from a Praxis epistemology perspective. The internship is seen as a central axis in the academic training of the future teacher, as it is through this moment that the intern has access to the knowledge essential for the construction of identity and everyday knowledge. For theoretical support, it was supported by some theoretical approaches such as: Barreiro and Gebran (2006), Antunes (2017), Nóvoa (1995), Pimenta and Lima (2004), Pimenta (2012), Barreiro and Gebran (2015), Tardif (2002), other teeth. This research is characterized as descriptive and explanatory. For Silva & Menezes (2000, p.21), descriptive research seeks to point out the characteristics of the reality of a given population and any phenomenon/fact that instigates interest or demands a problem to be investigated and understood. To classify this study, it was also decided to carry out a questionnaire to be answered by the teacher in charge of the internship locus, understanding that, as presented by Lakatos and Marconi (2002, p.201): the questionnaire “[...] is a data collection instrument, consisting of an ordered series of questions, which must be answered in writing and without the presence of the interviewer.” Therefore, this internship brought different sensations and interpretations experienced by each intern subject, from this perspective it is stated that the experience, both observational and practical, brought reflections on both positive and negative aspects, which govern attitudes as a professional in training, reflections that make us rethink our role in teaching. Finally, it can be said that the questionnaire addressed to the teacher regent of the research site made it possible to make an analogy between theoretical knowledge and the pedagogical practice of this teacher, as well as making us reflect on the importance of the internship in the training of the future teacher for the development of the epistemology of praxis. Thus, it is clear that the internship is a crucial moment in teacher training, it is the opportunity to experience the reality of the classroom from an epistemological perspective.